Estudo da influência da epibiose do protozoário ciliado Epistylis pygmaeum Ehrenberg, 1838 sobre o zooplâncton - Martins, Luciana Hitomi Hayashi (Universidade Federal de São Carlos, 2018)
Epibiosis is a type of facultative interaction between two species. The epibiont is the organism that colonizes a living substrate during the sessile stage of their life cycle, and the basibiont is the organism that serves as the basis for colonization. In the plankton of aquatic systems numerous epibiont ciliate species are often found colonizing various organisms, however the relationship between them and the ecological roles of epibiosis are poorly understood. The present study aimed to evaluate the epibiotic relationship in the zooplankton community, especially between cladocerans and the ciliate protozoan Epistylis pygmaeum Ehrenberg, 1838, in a shallow eutrophic environment, in Monjolinho reservoir, in the city of São Carlos-SP, Brasil. The presence of epibionts in the reservoir was monitored from november 2015 to november 2017. During the study, the occurrence and dominance of a species of epibiont (E. pygmaeum) was observed only in two periods: between july / august 2016 and august / september / october 2017. The samples were collected in horizontal trawls in the water column, using a mesh plankton net and brought to the laboratory where the populations were identified. After identification, basibiont survival experiments, epibiont localization site, host selectivity, rate of detachment and colonization and bacterivory were performed. E. pygmaeum showed preference for cladocerans, especially the genus Daphnia, and copepod ovine sac. It also showed preference for certain sites of colonization, the dorsal region being preferred to the other regions of the cladocerans' body. The protozoan was able to detach itself quickly from its host and transform from the sessile form to the free natant form (telotroquia) in an average time of 30 minutes. In relation to the influence of epibiosis on host survival we found that it affects adversely and significantly the survival of the host. In relation to the bacterivorous potential, in the three basibionte species tested Bosminopsis deitersi Richard, 1895, Daphnia ambigua Scourfield, 1947 and Moina micrura Kurz, 1874 we noticed a decrease in the consumption of bacteria by cladocerans carrying epibibionts when compared to the consumption of bacteria performed by cladocerans without the presence of epibiont in their carapaces. For the protozoan, the relation seems to be advantageous because its bacterial consumption was greater in its epibionte form when compared to its free natante form. Epibiosis, for the protozoan, although involving energy expenditure and supposed susceptibility to predation, confers benefits. For the host, a relationship is unfavorable and it ends up being impaired, both with respect to food and swimming, and may also affect its survival, especially in the presence of predators or in the occurrence of competition
Study of the influence of ciliate protozoan Epistylis pygmaeum Ehrenberg, 1838 epibiosis on zooplankton
Keywords: Epibionte; Protozoário; Cladócero; Bacterivoria; Seletividade; Epistylis sp; Epibiont; Protozoan; Cladoceran; Selectivity; Bacterivory; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::MICROBIOLOGIA